An Expert System For Diagnosing Tonsylliti Disease Using Web-Based Forward Chaining Method - Feri Ramadiansyah; Herlina Latipa Sari; Prahasti Prahasti (Jurnal Komputer, Informasi dan Teknologi, 2022)
Tonsillitis is inflammation of the palatine tonsils, which are part of the Waldeyer ring. Spread of infection through air borne droplets, hands and kissing. 4,5 Tonsillitis is more common in children aged 5-15 years with a prevalence of bacterial tonsillitis 15-30% in children with throat disorders and 5-15% in adults with throat disorders. The author received data that in the past year there were 63 patients suffering from tonsillitis, both acute and chronic. It can be concluded that every month there are 5-6 people from various regions in Bengkulu Province who suffer from tonsillitis and receive treatment at the Rafflesia Hospital. But the problem in the medical world is an imbalance between patients and doctors. In addition, most people are not medically trained, therefore the author intends to design an "expert system for diagnosing Tonsillitis using a web-based forward chaining method" which can be accessed through http://www.sistempakarfc1.my.id/. This application is expected to be used for the community in early diagnosis as prevention of more severe disease. This system is designed using the PHP programming language and MySQL database, the resulting expert system is able to help patients diagnose Tonsillitis and provide solutions to the disease. From the test results, the results obtained 100% functionality runs according to system requirements. In the system accuracy test carried out at Rafflesia Hospital, a very good accuracy value was obtained, which was 90% of the 10 sample data available.